Influence of the mesh structure of geodesic domes on their seismic response in applied directions - Bysiec, Dominika; Maleska, Tomasz (Archives of Civil Engineering, 2023)
The paper presents the determination of the impact of earthquakes of varying intensity on the structure of geodesic domes. The structures of the analyzed domes were designed on the basis of the regular octahedron according to two different methods of creating their topology. The use of four seismic records of different intensity and duration of the record made it possible to subject 8 models to numerical analysis. The designed spatial structures are domes with a steel cross-section, thanks to which they are undoubtedly characterized by their lightness and the possibility of covering very large areas, without the need to use internal supports. Designing steel domes is currently a challenge for constructors, as well as architect, who take into account their aesthetic considerations. The paper presents the seismic response of geodesic domes in applied different directions (two horizontal “X” and “Y” and one vertical “Z”), using the Time History method. The values of forced vibrations and recording intensity were shown, and on this basis, an attempt was made to determine which seismic record may be more unfavorable for the designed geodesic domes created according to two different methods of shaping the topology of their structures. For this purpose, the FFT (Fast Fourier Transform) method was used. The maximum accelerations and displacements of the structures were also analyzed. The conducted analysis shows the influence of seismic excitations on geodetic dome structures, depending on the applied method (method 1 and 2) of shaping their topology. This paper will undoubtedly be useful in designing a geodesic dome structure in a seismic area. In addition, this analysis can be helpful in assessing the effects of an incidental earthquake.
Keywords: forced vibrations; geodesic dome; lightweight structures; numerical analysis; seismic analysis